Children with Heavy Prenatal Alcohol Exposure Exhibit Deficits when Regulating Isometric Force - Simmons, Roger W. (2011)
BACKGROUND: Production of isometric (i.e., constant) force is an essential component of performing every day functional tasks, yet no studies have investigated how this type of force is regulated in children with confirmed histories of heavy prenatal alcohol exposure. METHODS: Children 7 to 17 years old with heavy prenatal alcohol exposure (n = 25) and without exposure (n =18) applied force to a load cell in order to generate an isometric force that matched a criterion target force displayed on a computer monitor. Two levels of target force were investigated in combination with three levels of visual feedback frequency that appeared on the computer monitor as a series of yellow dots. Force was maintained for 20 seconds and participants completed 6 trials per test condition. RESULTS: Root-mean square error, signal-to-noise ratio, and sample entropy indexed response accuracy, response variability and signal complexity, respectively. The analyses revealed that in comparison to controls, children with gestational ethanol exposure were significantly less accurate and more variable in regulating their force output and generated a response signal with greater regularity and less complexity in the time domain. CONCLUSIONS: Children with prenatal alcohol exposure experience significant deficits in isometric force production that may impede their ability to perform basic motor skills and activities in everyday tasks.